Plan estrategico de marketing para la empresa sucafe de la ciudad de Loja, provincia de Loja - Rosales Morocho, Karla Vanessa (2016)
The National University of Loja, has been making significant academic changes that have enabled it to improve quality of higher education, which uses research as the backbone of teaching and interaction with the community In conducting this thesis project they are framed in our occupational field and as future commercial engineers must know in an effort to meet the objectives of research, professional and technical training, consolidating this at the same time as a source of academic research for future students institution that are undertaken in the same field of study is the need to apply the acquired knowledge and contribute to society with possible solutions. This research has the general objective Develop "Develop a Strategic Marketing Plan for the company SUCAFE city of Loja province of Loja." Considering it as a tool to organize the activities of the same and decision-making for better performance. The methods used for the development of the research were the inductive method, which allowed us to establish the reality found in our company SUCAFE the statistical method, facilitated the tabulation of surveys of customers, employees and manager of the company; within the techniques allowed to apply to a survey of customers, employees and an interview with the Manager with the result of these data we can formulate the strengths, weaknesses, opportunities and threats, always relying on field research in the design matrix SWOT., which allowed for the deduction of the Mission and Vision, approach objectives, strategies, tactics, goals that allowed reaching establish findings and recommendations of the project and the solutions that were established for the parameters described in the proposal strategic plan, the Synthetic Analytical method allowed for the conclusions and recommendations for its particularity of description; Among the techniques used they are: the interview was made the manager of the company and surveys to employees and customers were conducted to explore issues of vital importance for the development of research. With the application of techniques situational diagnosis was obtained SUCAFE Company, the same consisting of the review of the company, the products offered, the current organization.; then the external analysis based on the factors affecting the company, the internal analysis through interviews and surveys, EFE matrix, where the weighting assigned to each of the external factors affecting the company was made, in which the weighted result of 3.08 which means that there is a predominance of opportunities over the EFI threats matrix was obtained, the weighting for each internal factors influencing the company was assigned, which is He got a score of 2.47 which means that the company has a predominance of strengths over weaknesses The SWOT matrix, allowed to determine the strengths, weaknesses, opportunities and threats that owns the company, also the impact matrix and SWOT matrix weights, a study for the recognition of Porter's five forces was developed; Following this matrix high-impact allowed to raise five strategic objectives with the aim of resolving the factors that impede their growth and maximize the resources of the company, among which it is determined, promote and strengthen the channel was developed marketing company whose budget is $ 25,920 annually, promote the company through a media plan whose budget is $ 3460.00 per year, implement a plan of promotions to increase sales with an annual budget of $ 9,200 , 00 dollars, improve training and service staff with a budget of $ 600,00 and acquire new manufacturing equipment coffee latest technology to optimize production with an annual value of $ 5,200.00, these goals represent an investment of $ 44,380.00 per year. Finally, conclusions and recommendations is presented, of which the most important is that SUCAFE., No account currently has a PLAN STRATEGIC MARKETING, that allows you to position themselves in the market town of Loja and among the recommendations the company makes a real advertising plan